Pengaruh Model Pembelajaran Think Pair Share Menggunakan Media Mind Mapping terhadap Aktivitas dan Hasil Belajar Kognitif Siswa - Rukiah Lubis; Meti Herlina; Jeni Rukmana (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2019)
This study aims to determine the effect of think pair share learning models using mind mapping media on the activities and cognitive learning outcomes of class X science students of SMAN 06 Bengkulu City. This type of research is a quasi-experimental design with Non-Randomized Design. Samples were taken from 2 classes of 4 classes by looking at the mean scores of students who are almost the same, namely class X Natural Sciences A as the experimental class and Natural Sciences B as a control class. The instrument used was in the form of student activity observation sheets and cognitive test questions. Based on scoring the results of the observation sheet of the experimental class student activity was higher than the control class that was 58.56 and the average posttest result was 85.69 while the observation sheet of the activity class of the control class was 53.97 and the average posttest result was 63.03. Student activity variable t-test results obtained Sig value of 0,000 <0.05 t-test results of student cognitive learning results obtained p-value of 0,000 <0.05, which means there are differences in activity scores and cognitive outcomes of students before and after the intervention of the learning model think pair share using media mind mapping. In conclusion, Think Pair Share learning model with Mind Mapping media has an influence on students' cognitive learning activities and outcomes. Keywords: activities, learning outcomes, mind mapping, think pair share